Teaching plant physiology to prospective biology teachers: How do we deal with Lesson Study-Problem based Learning (LS-PBL) to enhance scientific argumentation skill? - Maisuna Kundariati; Herawati Susilo; Balqis Balqis (Universitas Negeri Padang, 2021)
Argumentation has been widely discussed in science education for many years. Argumentation is a part of science, to make a statement and claim, justifying the claim, and supporting it with the data. Science education need to be integrated with scientific argumentation empowerment. LS-PBL can be one way to empower argumentation skills. The aims of this study is to determing prospective biology teachers’ science argumentation skill through Lesson Study-Problem based Learning (LS-PBL). This research was conducted on 30 prospective biology teachers at Biology Department Universitas Negeri Malang. Research participants are prospective biology teachers who are taking Plant Physiology course during their 3rd semester. The learning implementation was carried out in a blended learning. Lesson study activities carried out consist of three activities, namely, plan, do, and see. The instruments used are essay tests of scientific argumentation skills, chapter design, lesson design, lesson plans, and worksheets. Data analysis used quantitative descriptive analysis. The results showed the average value of the argumentation obtained in the first week was 45.33 (moderate), the second week was 50.00 (moderate), and the third week was 56.00 (moderate). The percentage of the frequency of each level of scientific argumentation decreased with each test at levels 1 and 2, while levels 3 and 4 increased. However, there is no level 5 argumentation found in tests 1, 2, and 3. An increase in argumentation skills can occur due to the application of PBL which is integrated with LS. The PBL learning model accommodates prospective biology teachers to construct their arguments, while lesson study is useful for improving the learning process so that learning activities increase from week to week and what is lacking can be improved. LS-PBL can be used as a professional tool to improve the learning process and empower argumentation skills.